2018
DOI: 10.1039/c8se00068a
|View full text |Cite
|
Sign up to set email alerts
|

A quadrafunctional electrocatalyst of nickel/nickel oxide embedded N-graphene for oxygen reduction, oxygen evolution, hydrogen evolution and hydrogen peroxide oxidation reactions

Abstract: A multifunctional nano-heterostructured electrocatalyst of transition metal/metal oxide (nickel/nickel oxide) embedded on nitrogen-doped graphene is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Their properties can be further modified, e.g., through heteroatom functionalization, or by engineering of defects as potential anchoring sites for active nanoparticles . Thus, a wide variety of MO X /C‐type materials has been proposed as catalysts for OER, ORR, and for reversible ORR/OER . Materials used for the latter are commonly known as bifunctional oxygen electrodes (BOEs), finding application in electrochemical devices which require the reversible conversion of water into oxygen and vice versa, such as rechargeable metal–air batteries and reversible fuel cells …”
Section: Introductionmentioning
confidence: 99%
“…Their properties can be further modified, e.g., through heteroatom functionalization, or by engineering of defects as potential anchoring sites for active nanoparticles . Thus, a wide variety of MO X /C‐type materials has been proposed as catalysts for OER, ORR, and for reversible ORR/OER . Materials used for the latter are commonly known as bifunctional oxygen electrodes (BOEs), finding application in electrochemical devices which require the reversible conversion of water into oxygen and vice versa, such as rechargeable metal–air batteries and reversible fuel cells …”
Section: Introductionmentioning
confidence: 99%
“…However, the electrocatalytic OER performances of the NiO nanostructures are still unsatisfiable because of their sluggish kinetics, low electronic conductivity, and limited active sites [ 32 , 33 ]. To release such drawbacks, thus, anchoring of NiO with carbonaceous materials (e.g., carbon particles [ 32 ], carbon nanotubes [ 33 , 34 ], carbon fibers [ 35 ], carbon nanowires [ 36 ], activated carbon (AC) [ 37 ], graphene [ 38 , 39 , 40 ], reduced graphene oxide [ 41 , 42 ], etc.) has been proposed as an effective way to improve the electrical conductivity as well as the vigorous kinetic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hoang et al [ 37 ] synthesized Ni/NiO/N-doped AC by using cauliflower leaves, and they showed a low overpotential of 346 mV at 10 mA/cm 2 and a small Tafel slope of 70 mV/dec. Faisal et al [ 40 ] also reported a low overpotential of 410 mV at 10 mA/cm 2 when using the Ni/NiO/N-graphene composites as an OER electrocatalyst. Very recently, Mugheri et al [ 32 ] achieved a very low overpotential of 220 mV and a small Tafel slope of 55 mV/dec from NiO/C electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene nanosheets (GNS), a two-dimensional material with sp 2 hybridized network of carbon atoms, is a novel support material due to its excellent physical and chemical properties such as high carrier mobility, excellent electrical conductivity, high chemical stability, high surface area and strong interfacial adhesion with electrocatalytic materials. GNS are almost transparent and has great potential in many applications such as solar cell 12 , sensors 13 , energy storage applications 14 and ORR 15 .…”
Section: Introductionmentioning
confidence: 99%